Traducir el Quijote - Albert Bensoussan (Mélanges de la Casa de Velázquez)
The author examines and compares French translations of Don Quixote, from that of César Oudin and François de Rosset (1614-1618), those of Filleau de Saint-Martin (1677-1678), Florian (1799), Louis Viardot (1836), and those of Xavier de Cardaillac and Jean Labarthe (1923-1926), Jean Cassou (1928) and Francis de Miomandre (1935), to the most recent ones by Aline Schulman (1997) and Jean Canavaggio (2001).